Analysis of a heuristic algorithm for job scheduling in a manufacturing plant - Topçu, Ayça (My University, 2000)
Bu tez bir traktör fabrikasında tezgah planlamada kullanılan çizelgeleme algoritmasını incelemektedir. Bunun için bu çizelgeleme algoritması ve literatürden alınan başka on algoritmanın uygulanabilirliği ve uygulanabilir veya uygulanamaz ise bunun sebebleri araştırılmaktadır. Araştırma için üretim atölyesinin nesne tabanlı bir simulasyon modeli hazırlamış ve bu model ile deney yapılmıştır. Daha çok uygulanabilir bir çözüm bulabilmek için atölyenin bir çevre parametresi değiştirilerek sensivity analizi yapılmış ve bunun içinde simulasyon tekrar çelıştırılarak yeni deney yapılmıştır. Deneyler sırasında sekiz atölye performs ölçüsünün değerleri test edilmiştir. Yapılan deneylerin sonuçlarını analiz etmek için varyans analizi ve Tukey testi gibi istatiksel yöntemler ve grafikler kullanılmıştır. Anahtar Sözcükler: Atölye, Atölye Çizelgeleme, Çizelgeleme Algoritmaları, Atölye Performans Ölçüleri, Simulasyon, Nesne Tabanlı Simulasyon, Varyans Analizi, Tukey Testi This thesis analyzes the scheduling rule used by a truck plant in the shop floor for job shop scheduling. For this the feasibility of the scheduling rule and ten more rules taken from the literature and the reasons of feasibility or unfeasibility of the rules are explored. For the exploration a object-oriented simulation model of the shop floor has been developed and used for the experiment. Then to find a more feasible solution for the job scheduling in the plant a sensivity analysis has been done by changing one environment parameter and running the simulation again for the new experiment. Eight job shop performance measures have been tested during the experiments. Statistical procedures, analysis of variance and Tukey test, and graphs have been used for the analysis of the results of the experiments. Job Shop, Performance Measures, Simulation, Object-Oriented Simulation, Analysis of Variance, Tukey Test Job Shop Scheduling, Scheduling rule, Job Shop
Keywords: Matematiksel Modeller